Pengaruh Konsentrasi Ekstrak Etanol Daun Pare (Momordica charantia L) Terhadap Daya Hambat Pertumbuhan Bakteri Staphylococcus aurus Metode Difusi - Trisna Widyanti; Dwi Sutiningsih; Mochamad Hadi (Universitas Sam Ratulangi, 2023)
One of the plants that can be used as a drug is a plant Pare (Momordica charantia L). This is because the leaves are nutritious for health. In general, the natural chemical compounds found in pare leaves are momordin, momordisin, trichosanic acid, resins, resinic acid, saponi, flavonoids, vitamins A and C, and fatty oils.The purpose of this study was to determine the effect of ethanol extract concentration of pare leaves (Momordica charantia L) to the inhibitory power of Staphylococcus aureus bacteria diffusion method. This research method is in the form of quasi experimental by using diffusion method to see extract inhibition zone. Leaf ethanol extract was obtained by maceration extraction method. The sample used was the concentration of pare leaf ethanol extract consisting of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100%. The results obtained at concentration of 10% have inhibitory power of 66.5% and increase with the increase of concentration up to 100% concentration has inhibitory power of 100%. Regression analysis got value (p = 0,00 <0,05) then Ha accepted, mean there is influence of ethanol extract concentration of pare leaf (Momordica Charantia L) of Staphylococcus aureus bacteria growth inhibition of diffusion method. Antibacterial activity of Momordica charantia L extract is more effective in inhibiting Staphylococcus aureus bacteria.